Evolutionarily conserved genes preferentially accumulate introns - Carmel, Liran; Rogozin, Igor B.; Wolf, Yuri I.; Koonin, Eugene V. (Genome Research, 2007)
Introns that interrupt eukaryotic protein-coding sequences are generally thought to be nonfunctional. However, for reasons still poorly understood, positions of many introns are highly conserved in evolution. Previous reconstructions of intron gain and loss events during eukaryotic evolution used a variety of simplified evolutionary models that yielded contradicting conclusions and are not suited to reveal some of the key underlying processes. We combine a comprehensive probabilistic model and an extended data set, including 391 conserved genes from 19 eukaryotes, to uncover previously unnoticed aspects of intron evolution—in particular, to assign intron gain and loss rates to individual genes. The rates of intron gain and loss in a gene show moderate positive correlation. A gene’s intron gain rate shows a highly significant negative correlation with the coding-sequence evolution rate; intron loss rate also significantly, but positively, correlates with the sequence evolution rate. Correlations of the opposite signs, albeit less significant ones, are observed between intron gain and loss rates and gene expression level. It is proposed that intron evolution includes a neutral component, which is manifest in the positive correlation between the gain and loss rates and a selection-driven component as reflected in the links between intron gain and loss and sequence evolution. The increased intron gain and decreased intron loss in evolutionarily conserved genes indicate that intron insertion often might be adaptive, whereas some of the intron losses might be deleterious. This apparent functional importance of introns is likely to be due, at least in part, to their multiple effects on gene expression.